Dermatology case - Gaspar, Joana; Tapadinhas, Cristina (BIRTH AND GROWTH MEDICAL JOURNAL, 2018)
The authors describe the case of a five-year-old girl, observed in Paediatric Dermatology Clinic due to a blood crust and vulvar ecchymosis associated with local pruritus. The observation revealed of a symmetrical and well defined white plaque around the vagina and anus, with mucocutaneous atrophy associated with the absence of labia minora and vascular purpura on the wishbone and clitorial hood. These findings were suggestive of vulvar lichen sclerosus. The aspects present in this entity can be easily confused with sexual abuse, reason why it is important to alert the Paediatricians and General Practice Doctors to the existence and the diagnostic features of this entity.